Adjustment of Consumers' Durables Stocks: Evidence from Automobile Purchases - Eberly, Janice C. (Journal of Political Economy, 1994)
This paper tests an optimal (S, s) rule in household durable purchases and examines directly the resulting aggregate expenditure dynamics. The observed decision rule responds to income uncertainty and growth as predicted by an (S, s) model resulting from transactions costs. Tests against liquidity constraints find that about half the households purchase according to an optimal (S, s) rule. Aggregating the (S, s) rule over households produces a cross-section distribution of durables holdings. The empirical distribution is similar to that predicted theoretically, as is its response to aggregate shocks. Furthermore, simulations of aggregate expenditure based on the household distribution exhibit dynamics consistent with those observed in the 1980s.